Nineteenth-Century Music - Dahlhaus, Carl 1928-1989 (California University of California Press, 1991)
This magnificent survey of the most popular period in music history is an extended essay embracing music, aesthetics, social history, and politics, by one of the keenest minds writing on music in the world today.Dahlhaus organizes his book around "watershed" years--for example, 1830, the year of the July Revolution in France, and around which coalesce the "demise of the age of art" proclaimed by Heine, the musical consequences of the deaths of Beethoven and Schubert, the simultaneous and dramatic appearance of Chopin and Liszt, Berlioz and Meyerbeer, and Schumann and Mendelssohn. But he keeps us constantly on guard against generalization and cliché. Cherished concepts like Romanticism, tradition, nationalism vs. universality, the musical culture of the bourgeoisie, are put to pointed reevaluation. Always demonstrating the interest in socio-historical influences that is the hallmark of his work, Dahlhaus reminds us of the contradictions, interrelationships, psychological nuances, and riches of musical character and musical life.Nineteenth-Century Music contains 90 illustrations, the collected captions of which come close to providing a summary of the work and the author's methods. Technical language is kept to a minimum, but while remaining accessible, Dahlhaus challenges, braces, and excites. This is a landmark study that no one seriously interested in music and nineteenth-century European culture will be able to ignore.